2011
DOI: 10.1038/cdd.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

Organisation and regulation of the cytoskeleton in plant programmed cell death

Abstract: Programmed cell death (PCD) involves precise integration of cellular responses to extracellular and intracellular signals during both stress and development. In recent years much progress in our understanding of the components involved in PCD in plants has been made. Signalling to PCD results in major reorganisation of cellular components. The plant cytoskeleton is known to play a major role in cellular organisation, and reorganization and alterations in its dynamics is a well known consequence of signalling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 67 publications
(104 reference statements)
3
81
0
1
Order By: Relevance
“…Furthermore, disturbance of the cytoskeleton was found in osgen1 microspores. Tubulin and actin did not form grid structures and only showed fuzzy signals, confirming cell death of osgen1 microspores (Smertenko and Franklin-Tong, 2011;Supplemental Fig. S9).…”
Section: Osgen1 Is Required For Dsb Repair Postmeiosismentioning
confidence: 74%
“…Furthermore, disturbance of the cytoskeleton was found in osgen1 microspores. Tubulin and actin did not form grid structures and only showed fuzzy signals, confirming cell death of osgen1 microspores (Smertenko and Franklin-Tong, 2011;Supplemental Fig. S9).…”
Section: Osgen1 Is Required For Dsb Repair Postmeiosismentioning
confidence: 74%
“…In plant cells, many extracellular stimuli trigger rapid changes in cytoskeletal organization, and these changes may serve as signals to regulate cellular responses, including programmed cell death (Wasteneys and Yang, 2004;Hussey et al, 2006;Smertenko and Franklin-Tong, 2011). Previous studies have shown that, in response to salt stress, the SOS pathway (Wang et al, 2007;Ye et al, 2013) and a pathway involving SOS3-like Calcium Binding Protein1, SOS2-like Protein Kinase5, and the plasma membrane H + -ATPase (Fuglsang et al, 2007) involve regulation of MF organization (Liu and Guo, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In Brewer's yeast (Saccharomyces cerevisiae), CAP (Srv2p in yeast) localizes to actin patches (Lila and Drubin, 1997) and is required for the formation of F-actin bodies (Gourlay et al, 2004) in stressed, quiescent Brewer's yeast (Sagot et al, 2006). Several plant systems have been observed to exhibit F-actin reorganization during PCD, and it is thought that the polymeric status of actin acts as a dynamic, integrated feedback mechanism for the health status of a cell, with PCD signaling major alterations (Smertenko and Franklin-Tong, 2011). Drawing comparisons with a study providing a link between actin alterations and signaling to apoptosis in lymphocytes (Hao and August, 2005), it has been suggested that a similar scenario may operate in plant cells and that alterations to the plant actin cytoskeleton could potentially signal directly to PCD (Tian et al, 2009 …”
Section: Identification Of Targets For Ph Alterationsmentioning
confidence: 99%